The siege - Alpert, Mark, 1961- (Alpert, Mark, 1961- Six trilogy, 2016)
Adam and the other robotized teenagers in the Pioneer Project must once again battle Sigma, the rogue artificial intelligence program bent on destroying Adam and all of humanity by first corrupting the Six from the inside.